Appendectomy Is Associated With Alteration of Human Gut Bacterial and Fungal Communities - Cai, Shuntian; Fan, Yanyun; Zhang, Bangzhou; Lin, Jinzhou; Yang, Xiaoning; Liu, Yunpeng; Liu, Jingjing; Ren, Jianlin; Xu, Hongzhi (Frontiers in Microbiology, 2021)
Recent research has revealed the importance of the appendix in regulating the intestinal microbiota and mucosal immunity. However, the changes that occur in human gut microbial communities after appendectomy have never been analyzed. We assessed the alterations in gut bacterial and fungal populations associated with a history of appendectomy. In this cross-sectional study, we investigated the association between appendectomy and the gut microbiome using 16S and ITS2 sequencing on fecal samples from 30 healthy individuals with prior appendectomy (HwA) and 30 healthy individuals without appendectomy (HwoA). Analysis showed that the gut bacterial composition of samples from HwA was less diverse than that of samples from HwoA and had a lower abundance of Roseburia, Barnesiella, Butyricicoccus, Odoribacter, and Butyricimonas species, most of which were short-chain fatty acids-producing microbes. The HwA subgroup analysis indicated a trend toward restoration of the HwoA bacterial microbiome over time after appendectomy. HwA had higher gut fungi composition and diversity than HwoA, even 5 years after appendectomy. Compared with those in samples from HwoA, the abundance correlation networks in samples from HwA displayed more complex fungal–fungal and fungal–bacterial community interactions. This study revealed a marked impact of appendectomy on gut bacteria and fungi, which was particularly durable for fungi.